On the influence of zirconium and tantalum impurities on the transport properties of multicomponent thermal plasma - Porytskyy, P.V.; Sviata, L.M. (Вопросы атомной науки и техники, 2019)
The influence of zirconium and tantalum impurities on the transport properties of multicomponent thermal plasma is considered in the ambient atmosphere of argon and air. The calculations are carried out on the base of Grad’s method, and it is shown that a small amount of metal causes the essential changes in the values of transport coefficients in comparison with the cases of pure gaseous mixtures. It is revealed that the influence of the Ramsauer effect on transport properties can be neutralized by additions of metal into ambient argon. Розглянуто вплив домішок цирконію та танталу на транспортні властивості багатокомпонентної термічної плазми в атмосфері сумішей аргону та повітря. Проведені розрахунки ґрунтувалися на методі моментів Ґреда. Показано, що невелика кількість металевих домішок може суттєво змінити величини транспортних коефіцієнтів порівняно із випадком чистого аргону або повітря. Висвітлено можливість нейтралізації впливу ефекту Рамзауера на властивості плазми шляхом додавання металевих домішок. Рассмотрено влияние примесей циркония и тантала на транспортные свойства многокомпонентной термической плазмы в атмосфере смесей аргона и воздуха. Проведенные расчеты основывались на методе моментов Грэда. Показано, что незначительное количество примесей металла может существенно изменить величины транспортных коэффициентов в сравнении со случаем чистого аргона или воздуха. Показана возможность нейтрализации влияния эффекта Рамзауэра на свойства плазмы путем добавки металлических примесей.